Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/nnr.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Velocity and Vasomotor Reactivity During Autonomic Challenges in Heart Failure

Abstract: Background Significant alterations in autonomic nervous system (ANS) function, vasomotor reactivity, and cerebral blood flow may develop from damage to brain ANS regulatory areas in heart failure (HF). This preferentially right-sided injury occurs largely in autonomic structures perfused by the middle cerebral artery. Indications of altered, asymmetrical perfusion raise the potential for further neural damage. Objectives To determine whether the extent of middle cerebral artery blood flow velocity and vasomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
10
1
1
Order By: Relevance
“…Comparing our results with previous reports on cerebrovascular reactivity in HF patients, our results are quite similar to those of Georgiadis et al These authors also found a significant decrease in VMR, even in NYHA class II patients, but also in NYHA classes III and IV. Moreover, Serber et al reported similar results, although the right/left asymmetry that they found was absent in the present study. The difference between these studies and the present study is that, in our study, these findings are further supported by a similar abnormality in NIRS‐based VMR, and by the finding of a disturbed dynamic autoregulation system.…”
Section: Discussionsupporting
confidence: 80%
“…Comparing our results with previous reports on cerebrovascular reactivity in HF patients, our results are quite similar to those of Georgiadis et al These authors also found a significant decrease in VMR, even in NYHA class II patients, but also in NYHA classes III and IV. Moreover, Serber et al reported similar results, although the right/left asymmetry that they found was absent in the present study. The difference between these studies and the present study is that, in our study, these findings are further supported by a similar abnormality in NIRS‐based VMR, and by the finding of a disturbed dynamic autoregulation system.…”
Section: Discussionsupporting
confidence: 80%
“…There is a very significant risk of a type 2 statistical error in a comparison of only 15 patients with 15 controls and significant differences may well have been found with larger patient numbers or if the patients had been older, had more severe CHF, or had fewer selection criteria applied. In addition, in my view, the isolated reduction in basilar artery flow in the presence of normal cerebral perfusion in the subtended brain areas remains speculative and may not prove to be a reliable finding, such as the fact that the right–left differences earlier described by Serber et al . were not confirmed in this study.…”
contrasting
confidence: 68%
“…In the present study, common carotid artery but not internal carotid artery was used for flow measurement given the easier access due to the size of the animal studied and as previously reported [34,42]. Interestingly, CBF does not reduce uniformly in patients with heart failure with the right hemisphere being more affected [48]. Multiple studies reported that heart failure induces more damage on the right side of brain affecting structures responsible for autonomic nerve regulation [48,49].…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 72%
“…Interestingly, CBF does not reduce uniformly in patients with heart failure with the right hemisphere being more affected [48]. Multiple studies reported that heart failure induces more damage on the right side of brain affecting structures responsible for autonomic nerve regulation [48,49]. Therefore the RCCA was used for CBF assessment in our study.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 86%